A study of Zero Working Capital in Malaysia - Lee, Pel Yeng (2010)
The main objective of this study is to explore the current situation in Malaysia in terms of the implementation of zero working capital. Background research showed that Malaysian companies are still having high working capital ratio, hence it is assumed that zero working capital\'s concept is not much in place.